Effect of an Online Language Course on Students` Grammar Achievement and Its Relationship with L2 Motivational Self System - Muhammad Ahkam Arifin; Hasnawir Hasnawir (Indonesian TESOL Journal, 2023)
MoreandmorecoursesarenowofferingonlineEnglishclasses.However,to date most studies have been limited to the investigation of the implementation of quizzes to improve students` grammar ability, while the use of video tutorials has been less explored. Thus, the current study aimed to investigate how video grammar presentations, in addition to quizzes, could help students improve their grammar achievement. 170 Indonesian students were enrolled in a grammar class as part of TOEFL ITP program conducted on an online language course. This course utilised videos to teach grammar points explicitly and deductively by using students` native language (Indonesian language). The effectiveness of the class was measured based on the results obtained from the pre-test and three progress tests. Each of the progress tests was conducted after a two-week treatment with around five grammar topics each. It was found that students` grammar achievement appeared to improve statistically significantly after receiving the first two-week treatment, yet students` scores were not found to be statistically significant between the progress tests. Thus far, it confirmed that online language programs with video-based grammar instruction as well as grammar exercises could lead students to increased grammar achievement. In addition, taking into account the importance of motivation as a powerful predictor of students` success, this study also investigated the relationship between students` motivation and their grammar achievement. Overall, no association between students` motivation and students` final progress test was found in this study.Keywords: Grammar achievement; Learning management system; Motivation; Online language course